Youth training centers: The development of a curriculum and training in morality and ethics, Nakhon Ratchasima Province - ไชยะพันธ์ อุทัย; บุญไชย พิสิฏฐ์; โพธิบัติ พนัส (Ratchaphruek Journal, 2018)
The purposes of this research were to study (1) the current situation and the problems of youth training centers, (2) the development of a curriculum and training in morality and ethics of youth training centers, and (3) the implementation of a curriculum and training in morality and ethics of youth training centers in Nakhon Ratchasima Province. This is an action research on 6 youth training centers, with a sample of 164 people selected by purposive sampling. The data were collected by surveys, interviews, observations, focus group discussions and workshop. All collected data were verified by content triangulation. The research results are presented as a descriptive analysis. The research findings show that youth training centers for learning and practicing morality and ethics are located in temples, religious organizations and government and private areas. The training curriculum aims to develop morality and ethics in participants with Buddhist content, including the treatment of oneself, families, educational settings, religious settings, communities and the nation. There is preparation of training, operations following the plan and the assessment of achievement and satisfaction after training. The problems with implementation are the insufficient number of lecturers, the lack of lecturer’s knowledge and ability, little or no payment, inadequate materials, inappropriate locations and insufficient budget. All of these problems are obstacles that affect the training. The researchers developed the curriculum “Num-Sang-Dhumma 01” based on these findings, which consists of 5 content areas, which are being a good son/daughter, a good student, friend, youth and member of the religion. The curriculum is also comprised of 16 activity plans and 28 sub-programs. The development of training centers involves 5 aspects, which are personnel, place, materials, budget and system management. The development of the training according to the curriculum will be conducted before the training, during the training, and after the training. In summary, the operative model of youth training centers is called 1P4D, consisting of P (problems), D1 (Development of training curriculum), D2 (Development of training centers), D3 (Development of training process) and D4 (Development of trainers). The curriculum “Num-Sang-Dhumma 01” was implemented in Num-Sang-Dhumma Camp at Wat Pa Khunna Sumpan Naram Temple (Pa Nong Hin), Boat Sub-district, Phimai District, Nakhon Ratchasima. The results found that (1) participants participated in all the activities determined in the curriculum and achieved the goals of the curriculum, (2) problems with the participants were found and the activities were conducted concordantly, and (3) participants were satisfied with the training program.